Determining drivers of eco-efficiency: decomposition method - Eduard Nežinský (University of Economics in Bratislava, Department of Economic Policy, 2014)
There has been a lively discussion about measures of social welfare beyond GDP induced by Stiglitz Report (Stiglitz et al, 2009) which can be viewed as a summation of the earlier efforts to deal with those challenges. Environmental indicators constitute one important dimension to be taken into account in assessing the welfare along with the economic and social indicators. Employing non-parametrical approach, the Data Envelopment Analysis SBM model is extended for environment to measure the so called eco-efficiency. Resulting scores and benchmarks are used to decompose eco-productivity into factors attributable to changes in efficiency, technology, extensive factors of production, and emissions. Results suggest that in European countries in the span 2000 – 2010, an environment-saving rather than input-saving technology change has been taking place.
Keywords: C43; C61; O47; 330; eco-efficiency; data envelopment analysis; beyond GDP; decomposition